2012
DOI: 10.1016/j.electacta.2011.10.071
|View full text |Cite
|
Sign up to set email alerts
|

Fast microwave-assisted solvothermal synthesis of metal nanoparticles (Pd, Ni, Sn) supported on sulfonated MWCNTs: Pd-based bimetallic catalysts for ethanol oxidation in alkaline medium

Abstract: The preparation of metal nanoparticles (Pd, Ni, Sn) supported on sulfonated multi-walled carbon nanotubes (SF-MWCNTs) using a very rapid microwave-assisted solvothermal strategy has been described. Electrocatalytic behavior of the SF-MWCNT-Pd and its 'mixed' bimetallic electrocatalysts (i.e., SF-MWCNT-PdSn mix and SF-MWCNT-PdNi mix ) towards ethanol oxidation in alkaline medium was investigated. The result shows that the mixed Pd-based catalysts (obtained by simple ultrasonic-mixing of the individual MWCNTmeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 122 publications
(52 citation statements)
references
References 55 publications
1
51
0
Order By: Relevance
“…At the same time, CoSi supported on graphene can prevent the aggregation of nanosheets and produce much more nanoparticle dispersion and utilization on its surface, therefore, nanoparticles can be loaded on both sides of graphene, which can also played an important role in the improvements of the electrocatalytic performance. We also found that the anodic peak current density of the Pt/CoSi-graphene is 5-20 times higher than other reported Pt-base electrocatalysts at the similar electrochemical reaction conditions [35][36][37][38][39][40][41][42].…”
Section: Resultsmentioning
confidence: 66%
“…At the same time, CoSi supported on graphene can prevent the aggregation of nanosheets and produce much more nanoparticle dispersion and utilization on its surface, therefore, nanoparticles can be loaded on both sides of graphene, which can also played an important role in the improvements of the electrocatalytic performance. We also found that the anodic peak current density of the Pt/CoSi-graphene is 5-20 times higher than other reported Pt-base electrocatalysts at the similar electrochemical reaction conditions [35][36][37][38][39][40][41][42].…”
Section: Resultsmentioning
confidence: 66%
“…The results of the Tafel polarization study corroborate the findings of CV. Nearly the same values of Tafel plots were obtained on graphene supported NiPd binary catalysts [6], binary composite films of Pd and Ni on multiwalled carbon nanotubes (MWCNT) [36], carbon supported PdNi nanoparticles [35,37] and rather higher on PdNi nanoparticles supported on sulfonated MWCNT [38]. Figure 6 shows the CVs obtained at Pd 0.74 Ni 0.26 catalyst in 1 M NaOH +1.0 M C 2 H 5 OH solution at different scan rates.…”
Section: Electrochemical Characterization Of the Electrodeposited Sammentioning
confidence: 61%
“…showed enhanced electrocatalysis towards alcohol than that by co-reduction of the metals [22,24]. In this work, we use XPS as a further proof for the formation of alloy.…”
Section: Xps Characterisationmentioning
confidence: 99%
“…To our knowledge the only known work is that by Sun et al [23] where the authors used Pd nanoparticles supported on sulfonate-functionalised multi-walled carbon nanotubes (SF-MWCNTs). Recently, it was shown that Pd bimetallic catalysts on SF-MWCNTs exhibit better performance towards ethanol electro-oxidation compared to monodispersed Pd nanoparticles [22,24]. Thus, motivated by the paucity of literature on EG electro-oxidation on Pd alloy catalysts in alkaline media, and the poor performance of monodispersed Pd nanocatalysts compared to the Pd bimetallic catalysts, we decided to investigate the electrocatalytic behavior of the Pd bimetallic catalysts (SF-MWCNT-PdNi and SF-MWCNT-PdSn) towards the oxidation of EG in alkaline medium.…”
Section: Introductionmentioning
confidence: 99%